Agile project management, assurance and auditing : a practical guide for auditors, reviewers and project teams - Wright, Christopher (Accountant) (IT Governance Publishing, 2022)
This guide provides an overview of Agile for auditors, reviewers and project teams.
Keywords: Agile project management.; Agile project management -- Auditing.; Agile software development -- Management.; Computer software -- Development -- Management.; Project management -- Methodology.; elektronické knihy; electronic books